Multiple repeat elements within the FAM21 tail link the WASH actin regulatory complex to the retromer - Jia, Da (The American Society for Cell Biology, 2012)
Wiskott–Aldrich syndrome protein (WASPs) control actin dynamics in cellular processes, including cell motility, receptor-mediated endocytosis, bacterial invasion, and vesicular trafficking. We demonstrated that WASH, a recently identified WASP family protein, colocalizes on endosomal subdomains with the cargo-selective complex (CSC) of the retromer, where it regulates retrograde sorting from endosomes in an actin-dependent manner. However, the mechanism of WASH recruitment to these retromer-enriched endosomal subdomains is unclear. Here we show that a component of the WASH regulatory complex (SHRC), FAM21, which contains 21 copies of a novel L-F-[D/E](3-10)-L-F motif, directly interacts with the retromer CSC protein VPS35. Endosomal localization of FAM21 is VPS35 dependent and relies on multivalency of FAM21 repeat elements. Using a combination of pull-down assays and isothermal calorimetry, we demonstrate that individual repeats can bind CSC, and binding affinity varies among different FAM21 repeats. A high-affinity repeat can be converted into a low-affinity one by mutation of a hydrophobic residue within the motif. These in vitro data mirror the localization of FAM21 to retromer-coated vesicles in cells. We propose that multivalency enables FAM21 to sense the density of retromer on membranes, allowing coordination of SHRC recruitment, and consequent actin polymerization, with retromer sorting domain organization/maturation.